Gas Switching Reforming (GSR) for syngas production with integrated CO2 capture using iron-based oxygen carriers. (February 2019) - Zaabout, Abdelghafour; Dahl, Paul Inge; Ugwu, Ambrose; Tolchard, Julian R.; Cloete, Schalk; Amini, Shahriar
Highlights: Gas Switching Reforming (GSR) concept for syngas production with inherent CO2 capture. Simpler scale-up than chemical looping reforming, but requires transient operation. Successful autothermal operation with iron-based oxygen carriers. The GSR fuel stage with iron-based oxygen carriers occurs in two distinct sub-stages; reduction and reforming. Abstract: The process behavior of a Gas Switching Reforming (GSR) reactor was studied using three different iron-based oxygen carrier materials: Iron-oxide on Alumina, Iron-Nickel oxide on Alumina and Iron-Ceria on Alumina. It was observed that, for all oxygen carriers, the fuel stage reaction occurs in two distinct sub-stages when feeding methane and steam to a bed of oxidized material, with methane combustion dominating the first and methane reforming dominating the second. This reflects a change in the catalytic activity of the oxygen carrier as it is reduced. The alumina support was observed to play a significant role in the reactions occurring, with the redox-active phases being hematite-structured Fe2 O3 (oxidized form) and spinel-structured (FeNiAl)3 O4 (reduced form). The Nickel-containing oxygen carrier outperformed the others in the reforming sub-stage, showing 40% improved methane conversion. The feed of dry methane only during the combustion sub-stage was found to improve methane conversion to syngas in the subsequent reforming sub-stage from 75% to 80% at 800 °C. Results also show that methane conversion improves with the increase in operating temperature and steam/carbon ratio. Autothermal operation of the reactor was achieved with repeatable performance over several redox cycles. The study therefore successfully demonstrated autothermal N2 -free syngas production with integrated CO2 capture from the fuel combustion required to supply heat to the endothermic reforming reactions.